Die gewonde God: "n Teologies-etiese besinning, veral vanuit Khoisan-perspektief - Boezak, Willa (HTS teologiese studies, 2017)
This article presupposes the right of the faithful to pose critical questions about God. God-concepts cannot be distanced or freed from ideology. In the Hebrew Scriptures, the reflection on Jahwe and Elohim are mostly influenced by Israel’s exodus experience. The liberating God becomes a theme that legitimises their faith, but is ultimately coloured by their patrarchal Sitz im Leben. For black theologians, the image of God as the Liberator stands foremost as the Crucified. This has clear connections with Western thinking such as that of Jürgen Moltmann. The ancient native people of southern Africa developed a consciousness regarding a Higher Being through many years, eventually integrating it into their holistic worldview. God’s involvement in human suffering plays a significant role in all of these expressions of faith. The different views of God as the transcendant, yet involved God, should be revisited within the context of our current society characterised by human suffering, chronic poor communities, gaping inequality and increasing corruption. The theological-ethical question is whether the Khoisan people’s view of a wounded God is more suitable to help faithful people to engage with the world in a meaningful way.